Perspective and Practices of Ornamental Fish Keeping by the Hobbyists in Tripura - Bonani Laskar , Biswarup Saha and Atanu Sarkar (Indian Journal of Extension Education, 2018)
Ornamental fish keeping in aquarium has been emerging as a popular hobby in Tripura. The study was conducted in the West Tripura district of Tripura among 100 randomly selected hobbyists of ornamental fish keeping. The data collected through observation and personal interview of the respondents revealed that majority of them were middle aged (36-50 years), all are literate and 50 per cent of them were graduates. Around 39 per centof the hobbyists were businessmen. Further, the majority of the respondents (38%) were found to be spending ` 50-100 per month to manage their aquariums. Majority of the hobbyists (89%) liked to keep Gold fish (Carassius auratus) in their aquarium followed by keeping shark (Carchardon carcharias) and Koi carp like Milky carp and Malina carp (Cyprinus carpio). Average purchase price of different varieties of fishes were also studied. Around 22 per cent of them did notice the symptoms of dropsy disease among the fishes being reared by them in the aquarium. Majority of the respondents sought information related to ornamental fishes through internet followed by personal contact like neighbours, friends and input dealers. Gross majority of them (80%) perceived cleaning of tank to be their major issue whereas, 43 per cent of them flagged that lack of scientific guidance regarding ornamental fish keeping and aquarium management was the major problem causing concern in continuing with the hobby. Therefore, a systematic drive for awareness generation and support system should be developed in the state to sustain and gear up the ornamental fish industry in the state.